Organic Vapor Sensors: Ordered‐Assembly Conductive Nanowires Array with Tunable Polymeric Structure for Specific Organic Vapor Detection (Small 27/2019). Issue 27 (5th July 2019) - Jiang, Xiangyu; Zhang, Xiqi; Wu, Yuchen; Li, Yunqi; Pang, Jinhui; Zhang, Haitao; Jiang, Lei
Abstract : In article number 1900590, Xiqi Zhang, Yuchen Wu, Lei Jiang, and co‐workers fabricate an Ag/polymer conductive nanowires array for specific organic vapor detection. Through molecular structure regulation of the synthetic polyethersulfone polymers, the prepared conductive nanowires array can distinguish similar organic vapors of methanol and ethanol.